Efek Daun Salam (Syzygium Polyanthum) dan Seledri (Apium Graveolens) Terhadap Hipertensi - Evy Eryta (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Hypertension is a major risk factor for cardiovascular diseases that often requires both pharmacological and non-pharmacological therapies. Herbal plants such as bay leaves (Syzygium polyanthum) and celery (Apium graveolens) have been used in traditional medicine due to their effects in lowering blood pressure. The aim of this study is to analyze the effectiveness of these two plants in reducing blood pressure through a systematic review and meta-analysis. Literature searches were conducted using relevant keywords in the PubMed, Scopus, and Cochrane Library databases. Meta-analysis showed that extracts of bay leaves and celery significantly reduced systolic and diastolic blood pressure. However, further research is needed to understand the mechanisms of action and their long-term effectiveness.